“Mr. Stubbs the Entertainer” and His Travelling Motion Picture Show - Clarke, Robert (Ontario History)

(untitled) (The Ontario Historical Society, 2022)
In the early days of cinema, before motion picture theatres were fully established, travelling exhibitors went from place to place with their stock of films, projectors, and other equipment, offering people a chance to see, sometimes for the first time, the new technological phenomenon of the age. A number of these exhibitors are relatively famous—and they had large business operations. A much lesser-known, and independent, travelling “showman” was James Stubbs, of Peterborough, Ontario, who took his regional and religious bandwagon on the road for about fifteen years, contributing as he went to the growth and acceptance of motion picture exhibition in the province.